Quality of institutions and foreign direct investment in developing countries: Causality tests for cross‐country panels - Hyun, Hea-Jung (Journal of Business Economics and Management, 2006)
This paper analyzes the short‐run and long‐run dynamics between quality of institutions and foreign direct investment (FDI) in the sample of 62 developing countries covering the period 1984–2003. Panel cointegration test and FM OLS (Fully Modified OLS) estimators are used to test for cointegration. For short‐run dynamics, we estimate error correction model using fixed effect OLS and system GMM estimators. Institutional quality and FDI are found to have bi‐directional cointegrating relationship in the long‐run. However, there is no evidence in favor of short‐run causality between two variables.Firstd Published Online: 14 Oct 2010